Translation Research Published in International Journals - Lévano Castro, Sofia (2022)
The aim of this study is to review translation research published in recognized translation journals to determine translation studies trends. To this end, 73 articles were analyzed from the following journals Translation Studies, The Interpreter  and Translator Trainer y Perspectives, Studies in Translation Theory and Practice. Qualitative data were selected and reduced to facilitate the textual analysis of these articles. The object of study, keywords, objectives, field of study and place of production were the categories of analysis. The results show a different object of study from those most studied in our environment. Most of the research is descriptive. As for the fields of study, they refer mostly to the didactics of translation and the sociology of translation and the translator as well as of the interpreter.